An Analysis Of Student’s Reception In An Online Learning Platform (OLP) Using The Technology Acceptance Model (TAM) - A. Amahan, DIT, Pilita; C. Amahan, Elmer (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The Technology Acceptance Model (TAM) is becoming more and more popular for understanding the acceptance between the perceived usefulness (PU) of humans and the ease of use of perceived technology (PEOU). This study aims to analyze student acceptance of online learning platforms (OLPs) and determine the appropriate combination they can offer as higher education believes in significant changes in the demand for online learning. Researchers used a quantitative and qualitative approach among 73 information technology students conducted from April to May of the 2021-2022 academic year. The questionnaire used was based on TAM variables and was validated using Cronbach’s alpha with a result of 0.727. Regression analysis was applied to identify which variables influence student interests. The results show that the perceived usefulness and visual appeal of the content are statistically significant at a p-value of 0.048. However, with a p-value of 0.716 achieved, it turns out that the perceived usefulness is not important to the perceived ease of use. Future recommendations should consider evaluating other information literacy acquisition variables, such as recognition of external controls such as computer and information anxiety